اثر استراتيجيتي (SQ4R) و(PQ4R) في تحصيل طلاب الصف الخامس الابتدائي والاحتفاظ بمادة العلوم - رشيد, مهند مجيد; يحيى, يحيى جاري (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The research aims to identify the impact of the strategy (SQ4R) and (PQ4R) in achieving and preserving the science material among fifth grade students, the researchers used the partial experimental design that the researchers randomly chose the control group representing Division (C) while the first experimental group in Division (B), while the Division (A) represents the second experimental group, and the number of members of the sample reached (60) A student, at the rate of (20) students for each equal number with a remote test in achievement, and the three research groups statistically using the unilateral contrast analysis in the following variables (timetable is calculated by months, intelligence test, previous knowledge, collection of parents) and the achievement test was prepared, verification of its honesty and stability and after treatment of the results of the student answers statistically using the analysis of the analysis The unilateral contrast, and to know the source of the differences between the averages, the Toki test was used, and the results showed that there is a statistical significance between the average